1999
DOI: 10.1023/a:1019972500785
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previous work had shown a large accumulation (up to 50% of mtDNA) of a noninherited T414G transversion at a critical control site for mtDNA replication in skin fibroblasts from the majority of human subjects above 65 years old, and its absence in younger individuals. In the present studies, long-term in vitro culture of several fibroblasts populations carrying the heteroplasmic T414G mutation revealed an outgrowth of the mutant cells by wild-type cells. This observation supported the previous conclusion that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The cell lines were described earlier by Michikawa et al (10). In particular, the AL4.8 and AL4.27 are homoplasmic wild-type at position 414 of the human mitochondrial genome, whereas the AL4.3 and AL4.5 carried the age-associated T414G transversion at a homoplasmic level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell lines were described earlier by Michikawa et al (10). In particular, the AL4.8 and AL4.27 are homoplasmic wild-type at position 414 of the human mitochondrial genome, whereas the AL4.3 and AL4.5 carried the age-associated T414G transversion at a homoplasmic level.…”
Section: Resultsmentioning
confidence: 99%
“…The AL4.3, AL4.5, 1AC1.2 human cell lines, carrying in homoplasmic form the T414G transversion in the mtDNA and the AL4.8, AL4.27 and 1AC1.48 cell lines, carrying in homoplasmic form the wild-type version (T) of the same position (414) of the mtDNA, were previously isolated by transfer into human mtDNA-less 143B.TK − ρ 0 206 cells of mitochondria from fibroblasts of the individuals 100-3y (for the AL series of transformants) and 98y (for the 1AC series of transformants) (6,10). All cell lines were grown in DMEM, supplemented with 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…We have found that AD brains, but not control brains, harbor a mtDNA control region mutation, T414G. This mutation alters the mitochondrial transcription factor (Tfam) binding site associated with the L-strand promoter, which transcribes the ND6 gene [87, 88]. This mutation was originally observed to accumulate with age in human skin fibroblasts [89].…”
Section: Inherited Mtdna Variation In Ad and Pdmentioning
confidence: 99%
“…Most strikingly, a T414G transversion was found in a high proportion (up to 50%) of mtDNA molecules from individuals above 65 years of age. However, when several fibroblasts populations carrying the heteroplasmic T414G mutation were grown in vitro , outgrowth of the mutant cells by wild-type cells was observed ( 101 ). This led to the suggestion that accumulation of mtDNA point mutations is a phenomenon occurring exclusively in vivo.…”
Section: Mtdna Damage and Senescence: Is There A Link?mentioning
confidence: 99%